Myeloid‐specific dopamine D2 receptor signalling controls inflammation in acute pancreatitis via inhibiting M1 macrophage. (22nd March 2020) - Han, Xiao; Ni, Jianbo; Wu, Zengkai; Wu, Jianghong; Li, Bin; Ye, Xin; Dai, Juanjuan; Chen, Congying; Xue, Jing; Wan, Rong; Wen, Li; Wang, Xingpeng; et al.
Abstract : Background and Purpose: Macrophage infiltration and activation is a critical step during acute pancreatitis (AP). We have shown that pancreas‐specific D2 receptor signalling protects against AP severity. As it is unclear to what extent myeloid‐specific D2 receptor mediates AP, we investigated the role of myeloid‐specific D2 receptor signalling in AP. Experimental Approach: Using wild‐type and LysM +/cre D2 fl/fl mice, AP was induced by l ‐arginine, caerulein and LPS. Murine bone marrow‐derived macrophages and human peripheral blood mononuclear cells (PBMCs) were isolated, cultured and then induced to M1 phenotype. AP severity was assessed by measurements of serum amylase and lipase and histological grading. Macrophage phenotype was assessed by flow cytometry and qRT‐PCR. NADPH oxidase‐induced oxidative stress and NF‐κB and NLRP3 inflammasome signalling pathways were also evaluated. Key Results: We found that dopaminergic system was activated and dopamine reduced inflammatory cytokine expression in M1‐polarized macrophages from human PBMCs. Dopaminergic synthesis was also activated, but D2 receptor expression was down‐regulated in M1‐polarized macrophages from murine bone marrows. During AP, myeloid‐specific D2 receptor deletion worsened pancreatic injury, systematic inflammation and promoted macrophages to M1 phenotype. Furthermore, M1 macrophages from LysM +/cre D2 fl/fl mice exhibited increased NADPH oxidase‐induced oxidative stress and enhanced NF‐κB and NLRP3 inflammasome activation. D2 receptor activation inhibited M1 macrophage polarization, oxidative stress‐induced NF‐κB and NLRP3 inflammasome activation. Conclusion and Implications: Our data for the first time showed that myeloid‐specific D2 receptor signalling controls pancreatic injury and systemic inflammation via inhibiting M1 macrophage, suggesting D2 receptor activation might serve as therapeutic target for AP.